2019
DOI: 10.1002/ags3.12303
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategy for isolated bile leakage after hepatectomy: Literature review

Abstract: Isolated bile leakage (IBL) after hepatectomy is intractable, and various treatment methods for it have been reported. This review aimed to clarify the treatment strategy for IBL by summarizing studies on IBL after hepatectomy without extrahepatic bile duct resection. Thirty‐three cases of IBL were reported. The incidence of IBL is very low, accounting for 0.1%–1% of all hepatectomy cases. The risk factors for IBL are unclear; however, several reports mention that biliary anomaly is associated with a high risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…The bile leakage test and C tube insertion could not prevent "isolated bile leakage" which does not communicate with distal bile ducts. 30 Another preventative method for bile leakage would be to cover the cut liver surface. Erdogan et al 31 reviewed the effects of topical hemostatic agents for bile leakage and concluded that there is no clear proof of their biostatic efficacy for bile leakage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bile leakage test and C tube insertion could not prevent "isolated bile leakage" which does not communicate with distal bile ducts. 30 Another preventative method for bile leakage would be to cover the cut liver surface. Erdogan et al 31 reviewed the effects of topical hemostatic agents for bile leakage and concluded that there is no clear proof of their biostatic efficacy for bile leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic duct tube (C tube) insertion to decompress the bile duct might be another preventative method for bile leakage; however, Nanashima et al 29 reported that the C tube failed to prevent bile leakage. The bile leakage test and C tube insertion could not prevent “isolated bile leakage” which does not communicate with distal bile ducts 30 . Another preventative method for bile leakage would be to cover the cut liver surface.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no standard treatment available for such intractable bilomas. Various treatments have been reported for intractable bilomas, including liver resection, bilioenteric anastomosis, endoscopic treatment, bile duct ablation, PTPE, and transcatheter arterial embolization (TAE) [ 6 ]. In our case, biloma was incurable with PCD and antibiotics for more than 3 months until a corresponding portral vein embolization was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the diverse and extensive involvement of the biloma in segments VI–VII, it was dangerous to perform TAE owing to the high complication rates due to parenchymal infarction. In high-output bilomas (as in our case), treatment ablation using alcohol or NBCA can be insufficient [ 6 ]. Our last non-surgical option was PTPE.…”
Section: Discussionmentioning
confidence: 99%
“…With deepening of the understanding of liver diseases and the development of hepatectomy techniques, the indications for liver resection have been continuously expanded, and the incidence of perioperative complications and mortality have been significantly reduced, but the incidence of bile leakage has not changed significantly (3.1 ~ 28.0%) ( 1 ). Miura et al reported in 2016 that the biliary leakage rate of 14,970 patients who underwent more than segment I hepatectomy recorded by the Japanese National Clinical Database from 2011 to 2012 was 8.0% ( 2 ).…”
Section: Introductionmentioning
confidence: 99%